Microbiology : principles and explorations. - Black, Jacquelyn G.; Black, Laura (Wiley, 2015)
"Microbiology: Principles and Explorations has been a best-selling textbook for several editions due to the author's engaging writing style where her passion for the subject shines through the narrative. The text's student-friendly approach provides readers with an excellent introduction to the study of Microbiology. This text is appropriate for non-major and mixed major microbiology courses, as well as allied health, agriculture and food sciences courses"--